Preliminary Observations on the Stemfllow Behaviour in Teak - Dabral, B.G. (Journal of Soil and Water Conservation, 2022)
Quite contrary to what happens in conditions where ground is devoid of vegetation, rain falling over a forested area is obstructed in reaching the ground directly through the canopy. This water flowing through the twigs, branches and stern isInown as stemflow. This wateris not caught in the troughs meant for recording throughfall and is therefore liable to be mistaken as interception loss (the water which is obstructed by the foliage and which does not reach the ground and gets evaporated). As such a correction for it requires to be made in estimating net rainfall and interception loss accruing as stated above.With a view to evaluating the quantity of water received on forest floor as stemflow, studies were conducted in a Teak (Tectona grandis) plantation of nearly 30 years age in the Demonstration area of this institute, during the rainy season of 1959. The importance of stemflow in adding to the ground water recharge is because it is delivered as a slow steady flow around the base, especially under milder storm conditions, where the soil is loose and friable, possessing high infiltration capacity (1,2,3).